[3-dimensional MR coronary angiography with navigator technique: imaging of the proximal course of a coronary artery anomaly] - Sandstede, J; Pabst, T; Beer, M; Kellner, M; Kenn, W; Neubauer, S; Hahn, D (1998)
Congenital coronary artery anomalies are found in 0.3 to 1.3% of patients and can cause ischemic heart disease or sudden cardiac death, especially if the anomalous coronary artery courses between the aortic root and the pulmonary artery. Identification of the anatomic course of the anomalous vessel is not always feasible by conventional radiographic coronary angiography. With MR coronary angiography not only flowing blood but also the vessel anatomy can be imaged. In previous studies, a two-dimensional gradient-echo sequence during breathhold was used demanding both cooperation of the patient and operator skill. The navigator technique reduces respiratory artifacts by retrospective respiratory gating on the diaphragm's position, obviating the need for breathhold studies. Furthermore, the three-dimensional MR coronary angiography enables post-processing using the Volume Rendering Technique for evaluation of three-dimensional view. We report on the use of this technique for the identification of the course of anomalous coronary arteries in two patient cases.